Highly Reproducible and Regulated Conductance Quantization in a Polymer‐Based Atomic Switch. (18th January 2017) - Krishnan, Karthik; Muruganathan, Manoharan; Tsuruoka, Tohru; Mizuta, Hiroshi; Aono, Masakazu
Abstract : A detailed understanding of the conductance quantization and resistive switching phenomena in redox‐based memories is crucial for realizing atomic‐scale memory devices and for finding the adequate design principles on which they can be based. Here, the emergence of quantized conductance states and their correlation with resistive switching characteristics in polymer‐based atomic switches are investigated using combinations of current–voltage measurements and first‐principles density functional theory (DFT) simulations. Various conductance states, including integer and half‐integer multiples of a single atomic point contact and fractional conductance variations, are observed in an Ag/polyethylene oxide/Pt device under sweeping of bias voltage. Moreover, highly controllable and reproducible quantized conductance behaviors by tuning the voltage sweep rate and the sweep voltage range, suggesting well‐controlled formation of the atomic point contact, are demonstrated. The device also exhibits longer retention times for higher conductance states. The DFT simulations reveal the transmission eigenstate of geometrically optimized atomic point contact structures and the impact of the atomic configurations and structural stability on the conductance state, which also explains their resistive switching behaviors. The well‐defined, multiple quantized conductance states observed in these polymer‐based atomic switches show promise for the development of new multilevel memory devices. Abstract : The emergence of quantized conductance states and their correlation with resistive switching characteristics are demonstrated in an Ag/polyethylene oxide/Pt atomic switch by means of the combinations of current–voltage measurements and first‐principles density functional theory simulations. It is found that the atomic configuration and structural stability of an atomic point contact play crucial roles in determining the quantized conductance state.